3D nanoporous iridium-based alloy microwires for efficient oxygen evolution in acidic media. (May 2019) - Zhao, Yang; Luo, Min; Chu, Shufen; Peng, Ming; Liu, Boyang; Wu, Qiuli; Liu, Pan; de Groot, Frank M.F.; Tan, Yongwen
Abstract: Although significant progresses have been achieved recently in developing catalysts for electrochemical oxygen evolution in alkaline electrolytes, high performance catalysts toward oxygen evolution in acidic media have not been realized in spite of the technical importance for the development of promising energy transformation technologies including electrocatalytic water splitting, integrated (photo)electrochemistry cells, rechargeable metal-air batteries, and so on. Here, we synthesized a three-dimensional nanoporous Ir70 Ni30-x Cox alloy microwires as oxygen evolution reaction electrocatalyst using a dealloying strategy. The three dimensional binder-free np-Ir70 Ni15 Co15 catalyst in 0.1 M HClO4 shows a low overpotential (220 mV@ η = 10 mA cm −2 ), low Tafel slope (44.1 mV dec −1 ) and excellent corrosion resistance, significantly outperforming commercial IrO2 catalysts. The excellent performance is attributed to the nanoporous structure and the alloying effect, which promote the permeation of electrolyte, accelerate the transportation of electrons. More importantly, the high valence Ir oxide species with low-coordination structure in np-Ir70 Ni15 Co15 alloy are identified for the real catalytic sites of OER process by the XAS results acquired on synchrotron radiation. This work not only provides fundamental understandings of the correlation between surface activity and stability for OER catalysts, but also paves a new way to advanced electrocatalysts working in acidic media. Graphical abstract: An Ir-based alloy microwires with ultrafine nanoporous structure is exploited for oxygen evolution reaction (OER) in acidic solutions. The binder-free np-Ir70 Ni15 Co15 catalyst exhibits the highest OER catalytic activity in acidic solutions with a low overpotential (220 mV @η = 10 mA cm −2 ) and a low Tafel slop of 44.1 mV per decade. These extraordinary catalytic activities toward acidic water splitting have not been achieved from many other state-of-the-art OER electrocatalysts before.fx1 Highlights: A dealloying strategy is proposed to synthesize free-standing Ir-based alloy microwires with ultrafine nanoporous structure. Ir70 Ni15 Co15 catalyst exhibits highly efficient and stable OER electrocatalytic activity in acidic electrolyte. The XAS results reveal that the high valence Ir oxide species with low-coordination structure as real active sites for OER.